ChemInform Abstract: Copper‐Mediated Halotrifluoromethylation of Unactivated Alkenes. Issue 17 (April 2016) - An, Won; Ha, Neul; Lee, Hyun Myung; Malpani, Yashwardhan R.; Lee, Duck‐Hyung; Jung, Young‐Sik; Han, Soo Bong
Abstract: A copper‐mediated halotrifluoromethylation of unactivated alkenes using Umemoto′s reagent and a copper(I) halide is developed.